Fabrication of refraction and diffraction glass lenses by using hot embossing process - Kasztelanic, Rafał; Kujawa, Ireneusz; Stępień, Ryszard; Waddie, Andrew J; Taghizadeh, Mohammad R; Buczyński, Ryszard (Photonics Letters of Poland, 2013)
The paper focuses on the results of fabrication of diffraction and refraction lenses with the use of hot embossing process from multi-component glasses.Hot embossing is an attractive alternative to other micro-replication methods, since its cost effectiveness makes it suitable for mass-fabrication of wide range of elements. Multi-component glasses names soft glasses are transparent from visible to near and mid infrared spectral region. Full Text: PDF References H. Becker, U. Heim, "Hot embossing as a method for the fabrication of polymer high aspect ratio structures", Sensors and Actuators 83,130 (2000) CrossRef M. Worgull, Hot Embossing, Theory and Technology of Microreplication, (William Andrew, 2009), M. Heckele, W.K. Schomburg, "Review on micro molding of thermoplastic polymers", J. Micromech. Microeng. 14, R1 (2004) CrossRef C.T. Pan, T.T. Wu, M.F. Chen, Y.C. Chang, C.J. Lee, J.C. Huang, "Hot embossing of micro-lens array on bulk metallic glass", Sensors and Actuators A 141, 422 (2008) CrossRef I. Kujawa, R. Kasztelanic, R. Stępień, M. Klimczak, J. Cimek, A.J. Waddie, M.R. Taghizadeh, R. Buczyński, "Optimization of hot embossing method for development of soft glass microcomponents for infrared optics", Opt. & Laser Techn. 55, 11 (2014) CrossRef R. Kasztelanic, I. Kujawa, R. Stępień, K. Haraśny, D. Pysz, R. Buczyński, "Fresnel lens fabrication for broadband IR optics using hot embossing process", Infrared Phys. & Techn. 60, 1 (2013) CrossRef R. Kasztelanic, I. Kujawa, R. Stępień, K. Haraśny, D. Pysz, R. Buczyński, Infrared Phys. & Techn. In press.